Fearfulness in commercial laying hens: a meta-analysis comparing brown and white egg layers - Ana K. Rentsch; Jennifer L. Ellis; Tina M. Widowski (Poultry Science, 2023)
ABSTRACT: High fearfulness in commercial laying hens can negatively affect production parameters and animal welfare. Brown and white egg layers differ in several behavioral characteristics, though reported differences in fearfulness are inconsistent. A meta-analysis was conducted to determine whether there are systematic differences in measures of fearfulness between brown and white layers. Twenty-three studies that examined either 1 or both of 2 behavioral tests were included: tonic immobility (TI) (longer duration = higher fearfulness, 16 studies) and novel object (NO) test (lower approach rate = higher fearfulness, 11 studies). The 2 tests were analyzed separately. TI analyses: A generalized linear mixed effect model (GLMM) with a lognormal distribution was fitted to describe the data with experiment nested in study as a random effect. Explanatory (X) variables were considered through backward selection, where potential X-variables included color (brown vs. white layers), decade (1980s, 2000s, 2020s), age (prelay vs. in lay), genetic stock (hybrid vs. grand-/parent stock), and methodology (back vs. side position). NO test analyses: univariable GLMMs with a beta distribution were fitted with approach rate as the Y-variable and color, decade, age, stock, or 2 methodological factors (test duration, single vs. group testing) as X-variables. Models were evaluated by assessing information criteria, residuals/random effect normality, significance of X-variables and model evaluation statistics (mean square prediction error, concordance correlation coefficient). TI duration was best explained by a color-by-decade interaction (P = 0.0006). Whites in the 1980s had longer TI durations (709.43 ± 143.88 s) than browns in the 1980s (282.90 ± 59.70 s), as well as in comparison to browns (208.80 ± 50.82 s) or whites (204.85 ± 49.60 s) in the 2020s. The NO approach rate was best explained by color (P ≤ 0.05 in 3 models), age (P < 0.05 in 3 models), and decade (P = 0.04). Whites had a higher approach rate (0.7 ± 0.07) than browns (0.5 ± 0.11), birds in lay a higher rate (0.8 ± 0.07) than birds prelay (0.4 ± 0.12), and approach rate for papers published in the 2000s (0.8 ± 0.09) was higher than in the 2020s (0.2 ± 0.12). The phylogenetic difference in the 1980s was no longer detectable after enforcing an upper limit on TI durations (10 min), as became common practice in later studies. Our findings suggest that phylogenetic differences in fearfulness and changes over time are test dependent, and this raises important questions and potential consequences for assessing hen welfare in commercial egg production.